Evaluating the willingness of Ghibe Valley (Ethiopia) residents to contribute time and money to a tsetse control programme using targets - Swallow, B.M.; Mulatu, W. (OAU/STRC, 1995)
A tsetse control experiment with 500 deltamethrin-impregnated targets was initiated in the Ghibe Valley, south-west Ethiopia, in April 1990. The theft of a large number of targets following the socio-political disturbances of May 1991 spoiled major reductions in tsetse density and trypanosome prevalence. It was proposed that a greater level of farmer and community participation would contribute to the effectiveness of the control. A survey of 180 household heads was conducted to ascertain residents' willingness to take more active roles in the experiment. Respondents were asked what ought to be done to reduce the problems of theft. The respondents generally indicated a willingness to participate more actively in guarding the targets and in detecting and punishing thieves. Respondents were asked the maximum amounts of money and/or labour that they would be willing to contribute to a re-designed experiment. Willingness to contribute money was found to be related to the gender of the household head, the number of cattle held by the household and whether the household was involved in the ongoing health and productivity study. Willingness to contribute labour was related to employment status, participation in other community groups and the information available to the respondent about the programme.